(THE IMPACT OF ORGANIZATIONAL TRUST ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (A FIELD STUDY ON GENERAL AUTHORITY OF CIVIL AVIATION IN JEDDAH - Al-Asimi, Samah Abdul Qader; Al-Hunaiti, Mohammed Faleh (Journal of Economic, Administrative and Legal Sciences, 2019)
The main objective of this study is to illustrate the impact of the Organizational Trust on Organizational Citizenship Behavior. The study also aims to identify the level of the Organizational Trust which include: (Trust in Organization, Trust in Immediate Supervisor, Trust in Coworkers). And the level of practicing Organizational Citizenship Behavior which include: (Altruism, Sportsmanship, Conscientiousness, Civility, Civilized behavior) among the employees of the General Authority of Civil Aviation. To achieve the study objectives, the researcher adopted the analytical descriptive approach and applied the questionnaire as a data collection tool. The study community consists of all employees of the General Authority for Civil Aviation at King Abdul Aziz Airport in Jeddah. The questionnaire was distributed to a random sample (n= 280). A total of 236 questionnaires were valid for analysis. A number of results have been reached, the most important of which are: the Organizational Trust and its dimensions positively influences the Organizational Citizenship Behavior in its dimensions. The results showed that the Organizational Trust was high at an average of (3.51/5), Trust in Coworkers was high (3.95/5), Trust in Immediate Supervisor was high (3.56/5), and Trust in Organization was average (3.14/5). The results showed that the practice of Organizational Citizenship Behavior was high (3.73/5) in all dimensions. Considering the results reached, the study made several recommendations, the most important of which are: The Authority's management should promote the Organizational Trust among employees by improving human resources practices; take into consideration the interests of employees when making decisions regarding human resources; provide a justification for the adoption of these decisions in recognition of the employees’ feelings.
Keywords: organizational confidence; confidence in the organization of the organization; confidence in the direct president; confidence in colleagues; the behavior of organizational citizenship